Spaces of Possibility In, Between, and Beyond Korea and Japan - Arai, Andrea 1956-; Sorensen, Clark W. 1948- (Center for Korea Studies publication series, 2016)
"Arising from a 2012 conference, this volume engages with spaces in, between, and beyond the national borders of Japan and Korea--what Henri Lefebvre has called 'social spaces of possibility in which difference suddenly arises.' Some of these spaces involve the ambiguous longings and aesthetic refigurings of the past in the present, the new social possibilities that emerge out of the seemingly impossible new spaces of development, the opportunities of genre. Museums, colonial remains, new architectural spaces, graffiti, street theater, popular song, recent films, photographic topography, and translated literature all serve as keys for unlocking the ambiguous and contradictory--yet powerful--emotions of spaces, whether in Tokyo, Seoul, or New York. Rather than emphasizing individual countries, chapters focus on the relationship between Korea and Japan. This volume will appeal to readers interested in urban studies, Korean and Japanese studies, popular culture, anthropology, social history, and literature. Contributors are Janet Poole, Tom Looser, Chris Nelson, Robert Oppenheim, Heather Hindman, Kyoung-Lae Kang, John Whittier Treat, Franz Prichard, and Heekyoung Cho"--Provided by publisher.